Saberes docentes: fundamentos da prática no ensino técnico - Barroso, Denise Araújo (2019)
The research sought to objectify the knowledge that guides the teaching practice in technical education, in the sense of identifying which are these fundamental knowledge built through the experience of teaching technical knowledge, seeking to verify the existence of a pattern in the didactic practice of these teachers and from these to propose teaching principles for technical education. The aim of these objectives is to understand what the literature presents on topics such as teacher training and teacher training for technical education trends in teacher training historical context of professional education philosophical and pedagogical principles for technical education; specificity of the technical know - how teachers and teaching knowledge in the technical education We direct our sample to the teaching subjects that do not have a degree and act in the teaching of technical subjects in the area of Agricultural Sciences in technical courses of middle level of IFAM - Campus Manaus Zona Leste. This qualitative research intends to minimize the lack of explanatory theories about the guiding principles of teaching practice in technical education, which justified the use of the Theory Based on Data, which seeks, from the data, to construct substantive level theory to explain the phenomena under study. For this, we used the semi-double interview and participant observation with the aid of audiovisual recording for data collection. The analysis of the data through the Grounded Theory generated the theory "Being a teacher in technical education: a product of experience", which acts as a central category and has its theoretical density confirmed in the data through the paradigm composed of five analytical categories that are integrated by the category central: "Rationale of the technique", acting as condition of the phenomenon; "Teaching professionalism", acting as context; "Financial dependency" that acts as an intervening factor; the actions of confronting the conditions, context and interventions are characterized by the category "Technique as practice"; that generate consequences called "Specificities of teaching in technical education. The research produced unfoldings that from the objectivation of the teaching knowledge triggered in a proposal of didactic principles for the technical education. These didactic principles are the basis for the educational product (required in professional masters) developed during the research called "Didactic know-how for technical education: a product of experience", which consists of a series of training videos and a training plan , which are available through the website www.didaticadoensinotecnico.com.